Understanding Behavioral Intention to Use Drone Technology for Sustainable Development: The Facilitating Role of Behavioral Learning Engagement with Instructional Videos - Kim, Jung Hwan; Chen, Charlie; Bhundarak, Komn (Thammasat Review, 2025)
Although drone technology can be regarded as one of the most viable technologies for achieving sustainable development goals (SDGs), individuals are still unaware of its benefits and challenges. During the pandemic, drone technology benefited businesses and communities as a mechanism of sustainable crisis management by minimizing human contact in different environments despite its safety concerns. However, few studies have shown what salient factors influence individuals’ intention to use drone technology in the context of sustainable development. Therefore, drawing on the theory of planned behavior (TPB), we investigate individuals’ behavioral intention to use drone technology for combatting pandemics while achieving SDGs. We also examine how individuals’ learning engagement with instructional videos facilitates their intention. Our findings suggest that only perceived usefulness positively influences individuals’ attitudes, which leads to their behavioral intention to use drone technology for SDG-related activity. In contrast, their perceived safety concerns and pandemic helpfulness do not significantly impact the formation of their positive attitudes toward drone technology use. Furthermore, we found that an individual’s sustainable development concerns and behavioral learning engagement are likely to play a significant role in facilitating their intention to use drone technology by their attitudes toward them. Based on our findings, this study contributes to the theoretical literature on technology adoption and learning engagement with instructional videos. This study also provides practical insights into how organizations and policymakers promote drone technology for sustainable development through informative and educational campaigns with instructional videos.